Chemodivergent transformations of amides using gem-diborylalkanes as pro-nucleophiles - Sun, Wei; Wang, Lu; Hu, Yue; Wu, Xudong; Xia, Chungu; Liu, Chao (Nature communications, 2020)
Amides are versatile synthetic building blocks and their selective transformations into highly valuable functionalities are much desirable in the chemical world. However, the diverse structure and generally high stability of amides make their selective transformations challenging. Here we disclose a chemodivergent transformation of primary, secondary and tertiary amides by using 1,1-diborylalkanes as pro-nucleophiles. In general, selective B-O elimination occurs for primary, secondary amides and tertiary lactams to generate enamine intermediate, while tertiary amides undergo B-N elimination to generate enolate intermediate. Various in situ electrophilic trapping of those intermediates allows the chemoselective synthesis of α-functionalized ketones, β-aminoketones, enamides, β-ketoamides, γ-aminoketones, and cyclic amines from primary, secondary, tertiary amides and lactams. The key for these transformations is the enolization effect after the addition of α-boryl carbanion to amides. Amides are versatile synthetic building blocks, however the general stability of the amide bond makes its selective transformation challenging. Here, the authors report a chemodivergent transformation of primary, secondary and tertiary amides by using 1,1-diborylalkanes as pro-nucleophiles.